Experimental measurement and model validation of COD in pipe under bending with off-centered circumferential crack (Fracture and Structural Integrity, 2014)
The leak area of circumferential through-thickness crack in pipe under bending depends on the position of the crack with respect to the bending plane. In leak-before-break (LBB) analysis, the assumption that the crack is symmetrically placed with respect to the bending plane is not necessarily conservative. In this work, the crack opening of circumferential cracks, off-centered with respect to the bending plane, was investigated experimentally. Here, three pipe geometries and two crack lengths were investigated. For each crack, the centred and two off-centered configuration were examined. The crack opening displacement (COD) distribution along the crack length was measured for two selected bending load levels using digital image correlation (DIC) technique. These measurements have been used for verifying the solution provided by the hodograph cone method (HCM) as proposed by Bonora [1].
Keywords: Hodograph Cone Method